From the Garden-City to the Idea of Sustainable Development: a Case Study of the Garden Tri-City Near Warsaw - Szczepańska, Magdalena (Regional Barometer. Analyses & Prognoses, 2018)
The conception of a garden-city assumes creation of an organized unit in functional and spatial terms ensuring harmonious relations among economic growth, protection of the natural environment and catering to different kinds of social needs. Thus, this former city model is deeply rooted in the contemporary idea of sustainable development. The article aims to describe a research procedure that would allow a determination of the degree of implementation of the garden-city concept in relation to contemporary cities. Moreover, the paper presents a comparative analysis of selected garden-cities in the context of the sustainable development idea. Historical, social, environmental and economic factors were analyzed as well as the functional-spatial structure and strategic documents of the cities. The entities investigated were shown to be the Polish interpretation of the garden-city idea and local rules include requirements concerning the principles of sustainable development.